Perbandingan Minat Beli Konsumen Antara Indomaret Dengan MM Acing Jaya Di Kota Pangkal Pinang - Darman Saputra; Vara Amelia; Septia Alchoiroh; Zelika Putri Restanti (STIE AMKOP, 2022)
Abstrak The purpose of this study was to determine and analyze the comparison of consumer buying interest in shopping at the Indomaret and MM.Acing Jaya minimarkets in the city of Pangkalpinang. The population of this research is the people in the city of Pangkalpinang and the sampling technique used is Accidental Sampling. This study uses a sample of people who have shopped at the Indomaret and MM.Acing Jaya minimarkets, totaling 100 respondents with the provisions of 50 Indomaret respondents and 50 MM.Acing Jaya respondents. The data analysis method used in this research is normality test, validity test and reliability test and independent test. The results of this study indicate that the most dominant or high consumer buying interest is consumer buying interest at the MM.Acing Jaya minimarket. The result of the difference is indicated by the probability value (sig-t) of 0.000 which is below the significance level with the parameter 0.028